L’agglomération portuaire de Port-Alfred – Bagotville - Harvey, Jacquelin (Cahiers de géographie du Québec, 1967)
The Saguenay fjord contains ten port agglomerations, among which that of Port-Alfred-Bagotville is the most important.The port of Port-Alfred started to expand in earnest in 1929, when the Aluminum Company of Canada Limited decided to improve and enlarge its facilities to meet the needs of its new Arvida plant. Today some 2,500 ships call at Port-Alfred yearly and over 3,500,000 tons of cargo are handled annually over its wharves. Imports of industrial commodities, notably aluminum ore from Guiana, make up the greater part of its traffic. The hinterland includes some ten important industrial establishments, distributed among the main centres of the Saguenay - Lake St. John area. Among these, ALCAN is the most important. Port-Alfred plays an important role in this industrial complex. In spite of certain handicaps, traffic pertaining to the aluminum and newsprint industries assures the harbour of con-tinuing prosperity in the years to come. One may even hope that further develop-ments in the hinterland will contribute to future growth of port activity.Located half a mile northeast of Port-Alfred, Bagotville seems more like an appendix of its powerful neighbour than an autonomous port. Its facilities and traffic are quite limited. The main port traffic up until 1965, but now discontinued, consisted of the calls of the Canada Steamship Lines' passenger vessels during the summer season.